Legal Concept of Providing a Family from Begging According to Islamic Law - Erwin Hamonangan Pane; Nur Hakima Akhirani Nasution (International Journal of Educational Research Excellence (IJERE), 2023)
Connection husband and wife, parents with child, as well between member family, bound with principles in aspect muamalah (action between human) in general, and principles in marriage in particular. As for principles prescribed marriage and family in the Qur'an is each other ridha, makruf (worth), trying create more conditions good (ihsan), sincere (nilah), deliberation, and peace (islah). Besides that marriage also has a purpose for form House sakinah stairs, mawaddah and mercy. In compile A work write scientific, use A method in compiling and collecting data is key main determinant for achievement something objective with effective ways, because method used for influence quality and quality an inscription. From the discussion presented in the proposed thesis research it can be concluded that: research shows according to Islamic law and the Act explained that the activity of begging and begging is a prohibited act. Various hadiths explain this prohibition. Begging is considered lazy work and does not rely on the strength that Allah SWT gives to make a living. Research also explains that there is a hadith which justifies the act of begging with the following three conditions someone is charged den a for pay off parent debt or his family, he can i beg until debt paid off, However after the debt paid off then he must leave deeds.